How new plant species have been discovered in China: collection gaps and preferences over the past century - Dongmin Shi; Dongmin Shi; Kuiling Zu; Kuiling Zu; Jiahui Nong; Jiahui Nong; Wenjing Yang; Yuting Zhang; Yuting Zhang; Shuai Liao; Guojin Zhu; Guojin Zhu; et al. (Frontiers in Plant Science)
IntroductionHow many species there are in the world remains a fundamental scientific question, serving as a critical reference for formulating and implementing effective biodiversity conservation strategies. The accelerating global biodiversity crisis has propelled scientific interest in understanding spatial-temporal patterns of new species discovery, particularly as these findings inform urgent conservation priorities. Digitalization of plant specimens provides important information on the discovery process of new species and clarifies the general situation of the core distributions in China over the last century. However, the new species discovery process of plants has not been the focus of much attention in Asia. The study analyzes digitized herbarium specimen data to investigate new species discoveries, specimen collection gaps, and collection preferences in China over the past century.MethodsFirst, we collected the herbarium type specimens data. Then we analyzed sampling biases of functional traits (life form, floral colors, fruit colors and types) in specimens collection and summarize distributional patterns in new species discovery. We answered the question of what plant species are more likely to be found and explored the distribution areas of new species discoveries over the last century.ResultsOur results reveal that there are more new plant species been found in herbaceous plants (90.8%) than woody (9.2%) plants, and new species with bright flowers and fruits, and the smaller height are easier to be discovered. There is also an observable inter-annual and seasonal variation in the discovery of new species, with peak collections occurring four year periods, and summer (June-August) witnessing the highest number of new species discoveries. The southern regions of China offer easier access to new species, and higher numbers of new species have been identified in the regions with the richness of plant diversity. The number of specimens collected by individuals (58%) surpasses those collected by teams (42%).DiscussionMore attention should also be paid to species with different plant functional traits (herbs, species with bright flowers and fruits) and the potential distribution of vacant regions. This study provides scientific reference and direction for the accelerating discovery of more new species in the future, and also contribute to the future conservation of biodiversity.